2013
DOI: 10.1007/s13277-013-0934-5
|View full text |Cite
|
Sign up to set email alerts
|

IDH1 mutation is associated with improved overall survival in patients with glioblastoma: a meta-analysis

Abstract: Previous studies proposed that isocitrate dehydrogenase 1 (IDH1) mutation was associated with improved survival in patients with glioblastoma, but those studies reported varying estimates and yielded inconclusive results. The purpose of the present study was to determine the effect of IDH1 mutation on the prognosis of patients with glioblastoma by performing a meta-analysis. Pubmed and Embase databases were searched for eligible studies. Studies reporting overall survival by IDH1 mutation in patients with glio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 26 publications
5
27
0
2
Order By: Relevance
“…Specifically, it was shown that IDH1 mutations associated with prolonged survival of GBM patients [9]. In this study we assessed the R132H mutation of IDH1 by immunohistochemistry.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, it was shown that IDH1 mutations associated with prolonged survival of GBM patients [9]. In this study we assessed the R132H mutation of IDH1 by immunohistochemistry.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we combined FZD7 with MGMT or IDH1, as these markers were shown to associate with the survival of GBM patients in previous [8, 9] and present (Figures 3–4) studies. We found that FZD7/MGMT combination was a strong independent predictor of poor survival in GBM patients, with twice as high hazard ratios compared to FZD7 alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, tumor molecular markers have been identified as better predictors of growth kinetics than classical histology. Specifically, patients with mutation of the isocitrate dehydrogenase 1 ( IDH1 ) gene [2] exhibit a marked survival benefit over patients with the wild-type tumor, independent of age and histologic grading [3, 4]. Such survival differences are believed to reflect growth characteristics unique to IDH1 subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…To improve patient's survival, it is important for us to identify some molecular markers of prognosis which may help us select the best suitable therapeutic strategies. Currently, several good biomarkers for the survival of glioma patients have been found, which are very helpful for us to predict patients' prognosis [14,[33][34][35]. Mutations in PTEN gene are correlated with poorer prognosis of glioma patients [35], while isocitrate dehydrogenase 1 (IDH1) mutation is associated with better prognosis of glioma patients [14].…”
Section: Discussionmentioning
confidence: 99%